Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1080/10852352.2016.1198166
|View full text |Cite
|
Sign up to set email alerts
|

“I’ll stop procrastinating now!” Fostering specific processes of self-regulated learning to reduce academic procrastination

Abstract: Academic procrastination is considered to be a result of self-regulation failure having detrimental effects on students' well-being and academic performance. In the present study, we developed and evaluated a group training that aimed to reduce academic procrastination. We based the training on a cyclical process model of self-regulated learning, thus, focusing on improving deficient processes of self-regulated learning among academic procrastinators (e.g., time management, dealing with distractions). The trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 30 publications
4
29
0
2
Order By: Relevance
“…As for academic performance in particular, the data found and the literature suggest SRL is related to academic adaptation. That highlights the importance of higher education institutions to provide an environment that promotes SRL strategies since low SRL levels are associated with lower student motivation, with increased intention to drop out, especially in the 1st year, and higher levels or procrastination (Zoltowski et al, 2016;Correia and Moura Júnior, 2017;Grunschel et al, 2018). Taking into account the positive attributes investigated, the results indicate all PP constructs assessed in the present study were significantly correlated with SRL, matching the hypothesis by the authors.…”
Section: Discussionsupporting
confidence: 86%
“…As for academic performance in particular, the data found and the literature suggest SRL is related to academic adaptation. That highlights the importance of higher education institutions to provide an environment that promotes SRL strategies since low SRL levels are associated with lower student motivation, with increased intention to drop out, especially in the 1st year, and higher levels or procrastination (Zoltowski et al, 2016;Correia and Moura Júnior, 2017;Grunschel et al, 2018). Taking into account the positive attributes investigated, the results indicate all PP constructs assessed in the present study were significantly correlated with SRL, matching the hypothesis by the authors.…”
Section: Discussionsupporting
confidence: 86%
“…During this reflection phase, the student attempts to understand why a certain result occurred and manages his or her emotions with respect to this result. In each of the self-regulation phases, procrastination problems can occur Grunschel et al (2018) . For example in the first phase, students with low levels of self-efficacy (e.g., Waschle et al, 2014 ) and deficient time management and goal-setting skills ( Lay and Schouwenburg, 1993 ) have more procrastination problems.…”
Section: Introductionmentioning
confidence: 99%
“…Considering these findings, Arnott and Dacko's (2014) suggestion that procrastination be addressed in first year students might help alleviate this tendency. Grunschel, Patrzek, Klingsieck & Fries (2018) found that procrastinators who completed a five-week group training based on a cyclical process model of self-regulated learning significantly reduced academic procrastination and reported improved time management skills.…”
Section: Procrastination and Its Effect On Academic Performancementioning
confidence: 97%